DIDACTIC ANALYSIS OF FRACTION LEARNING IN PROSPECTIVE MATHEMATICS TEACHERS - Rapa, Zulfahmi Mustapa; Masaniku, Rizal (Universitas Tanjungpura, 2025)
Understanding the concept of fractions is a significant challenge for prospective mathematics teachers. This study aims to analyze the didactic understanding of fraction learning among prospective mathematics teachers and evaluate the use of visual representations in improving the understanding of fractions. This study uses a qualitative approach with a case study design involving three students from the mathematics education program at a private university in Gorontalo Province as research subjects. The subjects were selected through purposive sampling based on the criteria of their level of understanding of fractions and representations, visual approaches and daily applications, and didactic abilities. Data were collected through a fraction concept understanding test and in-depth interviews, then analyzed using the Miles et al (2014). approach, which includes three stages: data collection, data reduction, and data presentation. The results of the study indicate that although students demonstrated a good basic understanding of fraction concepts, they experienced difficulties in connecting these concepts to more complex real-life applications. In addition, although visual representation approaches were used, there were still shortcomings in relating fractions to broader contextual situations. Based on these findings, it is recommended that mathematics teacher education focus on developing Pedagogical Content Knowledge (PCK) that can enrich students' understanding in teaching fractions with a more applicable and contextual approach.